Les grandes messes panarabes : festivals et biennales d’art arabe dans les années 1970 - Alia Nakhli (Revue des Mondes Musulmans et de la Méditerranée)
Festivals and pan-Arabic artistic biennales during the 1970s were the first events of their kind in the Muslim and Arabic-speaking world, signalling an opening between the Eastern and Western Mediterranean basins. Our purpose has been to give voice to the aspirations of artists seeking to promote a tradition of dialogue and exchange on issues of national and ethnic identity, even if such events were financed by regimes whose vision of art was essentially utilitarian and propagandistic. In our opinion, these events did not receive the recognition they deserved among art historians. A “Golden Age” in the early 1970s, marked by energy and enthusiasm was followed by a period of reduced activity and institutional inertia ending ultimately in the discontinuation of the event, despite various efforts to revive the exchange dynamic.